HEPARIN BINDING PROTEIN IN SEMEN OF BUFFALO BULL MIGHT BE RESPONSIBLE FOR BETTER SEMEN FREEZABILITY AND SUBSEQUENT FERTILITY - SINGH, AK; BRAR, PS; CHEEMA, RS (The Indian Journal of Animal Reproduction, 2022)
The present study determined the concentration of purified heparin binding proteins (HBP) in frozen-thawed spermatozoa of buffalo bulls and established the relationship of HBP with semen characteristics and fertility. About 50 frozen semen straws of same ejaculate per buffalo bull (n=30 bulls) were used to establish purified HBP concentrations in frozen-thawed spermatozoa extracts. On the basis of HBP, all the bulls were grouped as high fertility (HFB, >0.3 mg/109 sperms; n=15) or low fertility (LFB, <0.3 mg/109 sperms; n=15) bulls. The frozenthawed semen was evaluated for % acrosome reaction, HOST, spermatozoa viability and motility, as well as first service conception rate (FSCR). The results revealed that purified HBP concentration and semen characteristics like % acrosome reaction, motility and FSCR were higher (p<0.05) in HFB than in LFB. In conclusion, the higher concentrations of HBP in buffalo bulls might be responsible for their better semen quality and fertility.